Masculinity, asceticism, Hinduism : past and present imagining of India - Chakraborty, Chandrima, 1973- (Ranikhet : Permanent Black ; Bangalore: Distributed by Orient Blackswan, 2011)
Studies on the works of Bankim Chandra Chatterji, Rabindranath Tagore, and Mahatma Gandhi.
Originally presented as the author's thesis (Ph. D.)--York University, 2004.
Includes bibliographical references (p. [227]-248) and index.
Keywords: Chatterji, Bankim Chandra, -- 1838-1894 -- Criticism and interpretation; Tagore, Rabindranath, -- 1861-1941 -- Criticism and interpretation; Gandhi, -- Mahatma, -- 1869-1948.; Masculinity -- Religious aspects -- Hinduism; Hinduism and politics -- India